A plea for extension of the anatomical nomenclature. Part 1: Nervous system and senses - Kachlík, D; Musil, V; Baca, V (Folia morphologica, 2017)
A correct, exact, concise and detailed anatomical nomenclature is a cornerstone of communication not only in anatomy and related subjects but also in other medical branches and in the whole medical education. Terminologia Anatomica fulfils this task but some important structures are still missing there. The authors have collected and present here a list of terms including their definitions or explanations to provoke discussion about possible extension of the Terminologia Anatomica. The first part of this contribution, presented in this article, comprises 113 terms concerning the regulation systems of the human body: endocrine glands, central and peripheral nervous system, and senses. It also contains some corrections of anatomical mistakes, systemic inconsistencies and grammar changes.
Keywords: Nervous System; anatomical terminology; nervový systém; smyslové orgány; anatomy; terminologie jako téma; lidé; Terminology as Topic; Humans; Sense Organs; anatomical nomenclature